2018
DOI: 10.30989/mik.v7i2.281
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Yang Berhubungan Dengan Keterbukaan Status Hiv Seropositif Wanita Penderita Hiv/Aids Terhadap Pasangan Seksual Di LSM Victory Yogyakarta

Abstract: Background: The disclosure of women’s HIV status toward their sexual partners is an important issue that should be regarded as one of the efforts to prevent and control the spread of HIV. Research on the disclosure of seropositive HIV status as well as women-related factors in Indonesia, especially Yogyakarta is only a few. Objective: The purpose of this study is to analyse a factor related to the growth of HIV-positive female HIV/AIDS to sexual partners in LSM Victory Yogyakarta Methods: This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…A steady relationship is also considered as a solid relationship where problems related to childcare, support for children's needs and earning a living become a common problem, especially when facing a situation where one partner is unable to do his job because of illness (Miller & Rubin, 2007). The finding of the high number of women with HIV / AIDS who disclosed their status to sexual partners is in line with research conducted by Rukmi & Darussalam (Rukmi & Darussalam, 2018), where around 79.4% of women with HIV / AIDS in Victory Plus, Yogyakarta are open to sexual partners.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…A steady relationship is also considered as a solid relationship where problems related to childcare, support for children's needs and earning a living become a common problem, especially when facing a situation where one partner is unable to do his job because of illness (Miller & Rubin, 2007). The finding of the high number of women with HIV / AIDS who disclosed their status to sexual partners is in line with research conducted by Rukmi & Darussalam (Rukmi & Darussalam, 2018), where around 79.4% of women with HIV / AIDS in Victory Plus, Yogyakarta are open to sexual partners.…”
Section: Resultssupporting
confidence: 56%
“…HIV/AIDS cases are still considered as health problems in various countries in the world (Rukmi & Darussalam, 2018). Based on UNSAID (Joint United Nations Program on HIV and AIDS) statement, by the end of 2017, more than 36.9 million people in the world are living with HIV/AIDS (35.1 million are adult and 1.8 million are children).…”
Section: Introductionmentioning
confidence: 99%
“…27 status is because they are afraid of being rejected by their partners (44.7%) and fear of social stigma (35.9%). 28 Based on research conducted by Alemayehu et al in 2014 it was also explained that almost 64% women who are HIV positive disclose their HIV status to partners who have previously disclosed their status. 29 The results of this study are in accordance with research conducted on HIV/AIDS patients at Dr. M. Djamil Padang in 2017 which stated that the highest risk factor for HIV transmission through sexual intercourse was 61.9%.…”
Section: Research Articlementioning
confidence: 99%
“…Along with the development of HIV in the body, PLWHA will often face physical, psychosocial, psychological, and mental problems, both directly and indirectly, which will impact the quality of life of PLWHA (Rina, 2013). Based on previous research on the quality of life of PLWHA and the disclosure of PLWHA status, it was found that PLWHA in Yogyakarta had a mediocre quality of life (53.95%) and had high disclosure of status to sexual partners (79.4%) (Farillahsari & Yasin, 2014;Rukmi & Darussalam, 2018). However, research on the disclosure of status to non-sexual partners such as the nuclear family, extended family, close friends, work colleagues, the community's environment, and its relation to the quality of life at the Victory Plus Foundation have not been explored further.…”
Section: Introductionmentioning
confidence: 99%